2020
DOI: 10.1093/jme/tjaa172
|View full text |Cite
|
Sign up to set email alerts
|

Repellency and Contact Irritancy Responses of Aedes aegypti (Diptera: Culicidae) Against Deltamethrin and Permethrin: A Cross-Regional Comparison

Abstract: Control strategies exploiting the innate response of mosquitoes to chemicals are urgently required to complement existing traditional approaches. We therefore examined the behavioral responses of 16 field strains of Aedes aegypti (L.) from two countries, to deltamethrin and permethrin by using an excito-repellency (ER) test system. The result demonstrated that the escape percentage of Ae. aegypti exposed to pyrethroids did not vary significantly between the two countries in both contact and noncontact treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…[9][10][11] Because pyrethroid insecticide is widely used in space spraying, a rapid increase in A. aegypti mosquito resistance to pyrethroids is a considerable concern and may compromise the utility of IRS and LLINs. This paper is a continuation of our previous study, 12 which revealed that permethrin and deltamethrin exhibited low repellent and irritant effects on field mosquitoes with increased insecticide tolerance in Taiwan and Thailand. The underlying factors of these delayed responses are associated with the sensory impairment of neurons due to the pleiotropic effect following target-site gene mutation in insecticide-resistant mosquitoes.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…[9][10][11] Because pyrethroid insecticide is widely used in space spraying, a rapid increase in A. aegypti mosquito resistance to pyrethroids is a considerable concern and may compromise the utility of IRS and LLINs. This paper is a continuation of our previous study, 12 which revealed that permethrin and deltamethrin exhibited low repellent and irritant effects on field mosquitoes with increased insecticide tolerance in Taiwan and Thailand. The underlying factors of these delayed responses are associated with the sensory impairment of neurons due to the pleiotropic effect following target-site gene mutation in insecticide-resistant mosquitoes.…”
Section: Introductionsupporting
confidence: 61%
“…Eggs were collected with ovitraps from December 2017 to March 2018. The mosquito rearing method followed the protocol of Yu et al 12 The eggs were hatched in dechlorinated water containing two to three drops (1 mL) of vitamin C for 24 h, and then 200-250 larvae were transferred to a plastic container (29.5 × 23.0 × 5.0 cm 3 , length × width × height) containing 1 L of dechlorinated water. The larvae were given ad libitum access to pig liver powder mixed with dry yeast (1:1).…”
Section: Mosquito Rearingmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Sublethal doses of pyrethroids are also noted to have irritant effects on resting mosquitoes. [23][24][25] Life-history traits such as longevity and fecundity, and mosquito behaviours including mating, host-seeking and locomotion are critical factors governing the dynamics of mosquito populations in the field. 26 If sublethal doses of insecticide affect these traits differentially in susceptible and resistant mosquito populations, this will define the relative fitness of insecticide-resistant genotypes and determine the extent of resistance introgression into a population.…”
Section: Introductionmentioning
confidence: 99%